Patient Care Delivery: Electronic Nursing Documentation in Malaysia - Hussein, Siti Zuhaida; Khalip, Norazilah; Hashim, Rosnita; Harun, Rohaizah; Fazilah, Nor Fazlina; Mat Shah, Norazilah (UI Scholars Hub, 2021)
Background: The evolution of nursing documentation from paper to electronic format aims to improve patient safety and care quality. This study aimed to determine the knowledge and attitudes of registered nurses toward electronic nursing process documentation. Methods: This cross-sectional study was conducted among 189 registered nurses who work in medical wards at a teaching hospital in Kuala Lumpur. Simple random sampling was used. Respondents’ knowledge of electronic nursing documentation was measured using a questionnaire developed by Guedes, and their attitudes toward electronic nursing documentation were measured using a questionnaire developed by Hagos. Data analysis was performed using Statistical Package for the Social Sciences Statistics 26.0 for Windows and p < 0.05 was considered significant. Results: In this study, 50.8% of the respondents have a low knowledge level of electronic nursing documentation, and 89.4% have a positive attitude toward electronic nursing documentation. No significant relationship was found between sociodemographic factors, such as age, education level, working experience, knowledge level, and attitude, and electronic nursing documentation. Conclusions: Nurses had a higher knowledge level of and positive attitudes toward electronic nursing documentation. A longitudinal and comparative study was suggested for further research.